Edward’s Syndrome-A Case Report - Dutta, Shanta; Tutul, Fariah Arman; Dey, Dipika; Akter, Feroza; Rahman, Ziaur; Ahmed, Wazir (Bangladesh Journal of Child Health, 2022)
Edward’s syndrome is commonly known as the trisomy 18 syndrome. It is a devastating genetic disorder that can be characterized by multiple congenital anomalies. About 50% babies with this syndrome do not survive beyond one week of age and approximately 95% does not survive past the first year of life. The feature of Edward’s Syndrome involves in craniofacial, skeletal, cardiovascular, central nervous system and genitourinary malformations. The mortality rate among infants with trisomy 18 is high as a result of cardiac and renal malformations, feeding difficulty, sepsis and central nervous system defects. Here we report a neonate with Edward’s syndrome. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 178-181